About the History of Agro-Industrial Food Complex in Uzbekistan (80-90s of the XX Century) - Makhmutaliyevich , Khaydarov Izzatilla (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the formation of the agro-industrial food complex in Uzbekistan by the Soviet government in the 1980s-90s to provide the country with food and agricultural raw materials, as well as the establishment of an agro-industrial food complex in Uzbekistan and industry impact. The article also addresses the sectors of the agro-industrial food complex related to the production, processing, transportation, storage and sale of agricultural produce, divided into sectors. The study also provides a comparative analysis of the various sources and draws conclusions.